A Review of Fatigue Performance and Failure Mechanisms in Dental Restorative Materials Under Dynamic Occlusal Loading - He, Jia Tong (Journal of Neonatal Surgery, 2025)
This study presents a comprehensive comparative analysis of fatigue performance and failure mechanisms in contemporary dental restorative materials subjected to dynamic occlusal loading. Recognizing that fatigue failure constitutes a principal cause of clinical restoration failure, the investigation evaluates ceramics, resin-based composites, and metal-based restoratives under cyclic loading conditions designed to replicate physiological mastication forces. Using thermomechanical aging models, laboratory simulations, and finite element analyses, the study identifies key stress distribution patterns and failure initiation zones associated with each material type. Zirconia and lithium disilicate ceramics exhibit high initial strength but suffer from phase transformations and stress-induced microcracking, while resin-based composites are prone to interfacial degradation, particularly under humid and thermal conditions. Porcelain-fused-to-metal restorations demonstrate vulnerabilities to thermal fatigue and delamination due to mismatched material interfaces. Innovations such as AI-assisted crown design, surface roughness optimization, and titanium base integration show promise in enhancing fatigue resistance across material classes. The findings underscore the limitations of conventional static testing and highlight the need for dynamic, multidirectional fatigue simulations to better predict clinical outcomes. This study provides critical insights for material selection and restorative design in prosthodontics, offering a scientific basis for improving the durability, functionality, and long-term success of dental restorations.